Application Introduction and Learning Geometry of Space to Student Elementary School Using Method Rolling Hash Based on Android - Fajri, Heri; Santioso, Lucy Lidiawati; Rasna, Rasna; Awal Nur, Muhammad; Ghaniy, Rajib (Malikussaleh University, Aceh, Indonesia, 2025)
Along with technological advancements, smartphones have evolved from being just a means of communication to now being multifunctional devices that reflect the status of their users and offer various features, such as cameras, music and video players, video calls, voice recorders, games, and internet access. These innovations' progress made them widely used by humans in their activities. One of the innovations that utilizes this technology is a building space introduction and learning application explicitly designed for elementary school students, using the Android-based Rolling Hash method. This application is an interactive educational tool that provides comprehensive information about building spaces, explains the various forms of building spaces, provides applicable examples, and offers solutions to related problems. This application's primary focus is implementing the Rolling Hash algorithm for string matching, which was chosen for its ability to perform fast and accurate matching in answering questions. By implementing this algorithm, the application can efficiently handle various questions involving strings, enhancing students' learning experience. This application uses Java programming language with ADT IDE for Eclipse and SQLite as a database system to store and manage data. The result of this final project is a learning application that not only facilitates the introduction of building space concepts to elementary school students but also shows how modern technology can improve learning methods. The Rolling Hash algorithm proved its effectiveness in fast and precise string matching, providing an optimal solution for this educational application and presenting a model of how technological tools can support primary education innovatively and practically.